Relating Coral Skeletal Structures at Different Length Scales to Growth, Light Availability to Symbiodinium, and Thermal Bleaching - Swain, Timothy D.; Lax, Simon; Lake, Natalie; Grooms, Hannah; Backman, Vadim; Marcelino, Luisa A. (Frontiers in Marine Science, 2018)
Light scattering of coral skeletons and tissues increases light availability to photosynthetic endosymbionts to form one of the most efficient biological collectors of solar radiation. Rapid increases in light availability during thermally-induced symbiont loss (bleaching) impair photosynthetic performance of the remaining Symbiodinium and precipitate a more severe bleaching response (optical feedback-loop hypothesis). Here we focus on light scattering of the skeleton, which is determined by light interaction with skeletal components assembled in a hierarchical fractal-like structure from tens of nanometers (e.g., calcium carbonate nanograins) to micro- and milli-meters (septa, corallites, and coenosteum) to centimeters and higher (colony form). We examined the association between skeletal structures, their role in light scattering, and species-specific bleaching responses for 88 coral species using phylogenetically-corrected analysis. We also explored the effect of growth on light scattering by modeling the fractal-like accretive growth of the skeleton (assuming a diffusion limited process of biomineralization) as a function of skeletal density, size of nanograins, fractal range of biomineralized clusters, and overall mass-fractal dimension, and validated the model with experimental data. Our results show that differences in light scattering from the top ~200µm (micro-μ_s^') of the skeleton, and not from the whole skeleton (bulk-μ_s^'), are related to bleaching susceptibility. We also demonstrate how differences in micro-μ_s^' of corallites and coenosteum could explain, in part, heterogeneous light environment between polyp and coenosarc. The average effective light transport distance of coenosteum measured in 14 coral species indicates that coenosteum could transport light to the corallites, which could then function as ‘light-trapping devices’ where photons are scattered multiple times by septa and corallite walls until absorbed by Symbiodinium. Furthermore, our fractal skeletal growth model suggests that corals that grow faster typically have lower mass-fractal dimension, denser skeletons, lower skeletal micro-μ_s^', and higher bleaching susceptibility. Finally, our results demonstrate that several skeletal structures of varying length scales known to modulate the light microenvironment of Symbiodinium in coral tissue are not associated with bleaching susceptibility. This work provides evidence of the relationship between skeletal growth, light scattering, and bleaching, and further supports the optical feedback-loop hypothesis of coral bleaching.